Rare bird documentation form for Peregrine Falcon at West Spencer, 1991 - Schoenewe, Lee A.et al (1991)
Rare bird documentation form for a Peregrine Falcon at West Spencer in Clay County, IA on May 5, 1991. Epson - sheet feed